Study on Geochemical Behaviour of Gangue Potential Acidic Release - Sun, Ya-Qiao; Shen, Yuan-Yuan; Duan, Lei; Dou, Lin (Asian Journal of Chemistry, 2014)
Geochemical behaviour of gangue potential acidic release has been investigated through soaking experiments under different conditions of liquid/solid ratio and soaking period. The results show that leachate pH ranges 6.99-7.71 (neutral or weakly alkaline) during immersion test which lasted for 30 days. The closed state where soaking test was performed inhibited the oxidation and dissolution of sulfur minerals containing in coal gangue, thereby affecting acidic release of gangue and making leachate weakly alkaline, resulting in only a small number of heavy metals Co, Cu, Mn and Sr at exchangeable state dissolved by water (dissolution rate £ 62.79 %) with the exception of Cr (completely dissolved) in gangue soaking. Under alkaline conditions, dissolution rates of Co, Cr, Cu, Mn and Sr carbonates, iron and manganese oxide phase, organics matter and residual are extremely low (£ 16.67 %). During soaking test, dissolution release rates of sulfur containing minerals in gangue with acid production (H2SO4) capacity of 57.56 Kg/t range merely 2.70-10.34 %. Along with the proceeding of soaking, enhancement of dissolution-release rate of sulfur containing minerals will lead to the solubilization-release of harmful trace elements in gangue. Hence, acidic release of gangue has a potentially considerable impact on environment.